Bodyminds Reimagined (Dis)ability, Race, and Gender in Black Women's Speculative Fiction - Schalk, Sami (Duke University Press, 2018)
Bridging black feminist theory with disability studies, Sami Schalk traces how black women's speculative fiction complicates the understanding of bodyminds in the context of race, gender, and (dis)ability, showing how the genre's exploration of bodyminds that exist outside of the present open up new social and ethical possibilities.